Single nucleotide polymorphisms associated with nonsyndromic cryptorchidism in Mexican patients. (10th March 2017) - Chávez‐Saldaña, M.; Vigueras‐Villaseñor, R. M.; Yokoyama‐Rebollar, E.; Landero‐Huerta, D. A.; Rojas‐Castañeda, J. C.; Taja‐Chayeb, L.; Cuevas‐Alpuche, J. O.; Zambrano, E.
Summary: Cryptorchidism is a frequent genitourinary malformation considered as an important risk factor for infertility and testicular malignancy. The aetiology of cryptorchidism is multifactorial in which certain SNPs, capable of inhibiting the development of the gubernaculum, are implicated. We analysed 16 SNPs by allelic discrimination and automated sequencing in 85 patients and 99 healthy people, with the objective to identify the association between these variants and isolated cryptorchidism. In two different patients with unilateral cryptorchidism, we found the variants rs121912556 and p.R105R of INSL3 gene in a heterozygous form associated with cryptorchidism, so we could considered them as risk factors for cryptorchidism. On the other hand, SNPs rs10421916 of INSL3 gene, as well as the variants rs1555633 and rs7325513 in the RXFP2 gene, and rs3779456 variant of the HOXA10 gene were statistically significant, when the patients and controls were compared and could be considered as protective factors since are predominantly present in controls. The genotype–phenotype correlation did not show statistical significance. With these results, we could conclude that these polymorphisms can be considered as important variants in our population and would contribute in the future knowledge of the aetiology and physiopathology of cryptorchidism.